Etiology of Acute Kidney Injury in Hospitalized Patients in a Tertiary Care Hospital - Karim, Md Ataul; Rahman, Md Habibur; Hassan, Md Habib; Zahed, A S M; Uddin, Md Jashim; Sarkar, Shoman (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Acute Kidney Injury (AKI) previously referred to as acute renal failure complicates acute care hospital admissions and intensive care unit patients. In AKI associated with sepsis and multiple organ failure, mortality is high and the outcome is usually determined bythe severity of the underlying disorder and other complications, rather than by kidney injury itself. Aim of our study was to evaluate the etiological profile of AKI in a tertiary care hospital like Chittagong Medical College Hospital (CMCH). Materials and methods: This observational study was conducted among 100 hospitalized patients in different wards of CMCH from November 2018 to April 2019. Patients were selected based on the Kidney Disease Improving Global Outcomes (KDIGO) criteria of AKI. An increase in serum creatinine >0.3 mg/dl or >1.5 times the baseline and a fall of urine output <0.5 ml/kg/h for 6–12 h were the criteria for selection. A structured questionnaire was completed andbaseline level of serum creatinine, urine output were documented. Results: Out of 100 patients, 56 were males and 44 were females. Mean age of the patients was 40.89±12.74 years. Diabetes mellitus and Hypertension were the common comorbidities. Hypovolaemia and Sepsis were found to be most common cause which included diarrheal illness (27 patients) followed by Urinary Tract Infection (9 patients) and Community-Acquired Pneumonia (4 patients). Eleven patients had Surgical causes and only 8 had Obstetrical causes. Conclusion: Causes of AKI arepreventable and treatable. Timely appropriate management will reduce the incidence and improve the outcome of AKI. JCMCTA 2020 ; 31 (1) : 108-112